2013
DOI: 10.1155/2013/321051
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Harvesting Corn Stover under Time Constraint: The Case of North Dakota

Abstract: This study examines the impact of stochastic harvest field time on profit maximizing potential of corn cob/stover collection in North Dakota. Three harvest options are analyzed using mathematical programming models. Our findings show that under the first corn grain only harvest option, farmers are able to complete harvesting corn grain and achieve maximum net income in a fairly short amount of time with existing combine technology. However, under the second simultaneous corn grain and cob (one-pass) harvest op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Machinery and equipment costs were estimated with the MachData model (Lazarus, ), which uses economic engineering‐based estimates of per‐hour and per‐acre costs of labor, tractor, and equipment use. This machinery cost estimator is used widely by farm management advisors and farm managers (Myhre, ; Venuto & Daniel, ; Maung & Gustafson, ). The results indicate a representative cost per activity rather than that specifically incurred in the field – or in this case, on the research plot.…”
Section: Methodsmentioning
confidence: 99%
“…Machinery and equipment costs were estimated with the MachData model (Lazarus, ), which uses economic engineering‐based estimates of per‐hour and per‐acre costs of labor, tractor, and equipment use. This machinery cost estimator is used widely by farm management advisors and farm managers (Myhre, ; Venuto & Daniel, ; Maung & Gustafson, ). The results indicate a representative cost per activity rather than that specifically incurred in the field – or in this case, on the research plot.…”
Section: Methodsmentioning
confidence: 99%
“…However, such a practice also has drawbacks, as delayed harvest can reduce plant yields 117 . The choice of a particular harvest method needs to consider other factors, such as the economic impact on the farmers, so that the most advantageous method can be applied 118 …”
Section: Strategic Handling To Mitigate the Impact Of Plant Minerals ...mentioning
confidence: 99%
“…117 The choice of a particular harvest method needs to consider other factors, such as the economic impact on the farmers, so that the most advantageous method can be applied. 118 Mineral reduction can also be achieved by feedstock preprocessing such as separating biomass by particle size and anatomical fraction, continued by selecting the fractions with lower mineral content. 101 The effectiveness of biomass handling in managing mineral content using air classification and size fractionation in multiple feedstocks (corn stover, switchgrass, and grass clipping) has been proven because fractions with higher mineral content are usually obtained from the smallest size and lightest airclassified fractions.…”
Section: Improved Biomass Harvesting Collecting and Preprocessing Met...mentioning
confidence: 99%
“…Among the 32 papers, more than 55% were published after 2008, suggesting a growing interest in optimization analyses of LCB feedstock and biofuel supply chains. The objectives of the mathematical programming models in many studies, including more recent studies after 2011, were single objective optimizations using economic criteria such as cost minimization, net present value maximization, or profit maximization (e.g., Dunnett, Adjiman, and Shah, 2007;Kondili, Pantelides, and Sargent, 1993;Mas et al, 2010;Maung and Gustafson, 2013), whereas a few studies considered dual economic and environmental criteria in the design of a feedstock supply chain. For example, You and Wang (2011) evaluated minimum economic cost and minimum GHG emission criteria to examine the optimal biofuel supply chain as a case study in Iowa and found that efficient conversion technology was the key for commercialized LCB-based biofuel production.…”
Section: Literature Reviewmentioning
confidence: 99%